Multi-criteria mission abort policy for systems subject to two-stage degradation process - Zhao, Xian; Fan, Yu; Qiu, Qingan; Chen, Ke (European journal of operational research, 2021)
•Multi-criteria mission abort policy is developed incorporating stage dependent degradation information.•Mission reliability, system survivability and monotonicity properties of the two metrics are analyzed.•The structural properties of the optimal abort policy are investigated.•The performance of the optimal policy is compared in detail against several heuristic policies. Failures of mission-critical systems may result in irretrievable economic losses and significant damages. Mission abort is an effective way to reduce the risk of casualties and enhance the system survivability. A core concern in real operation is how to balance the mission reliability and the system survivability via elaborate mission abort plans. This paper investigates the condition based mission abort policies for systems subject to two-stage degradation process with normal and defective stages. Dynamic mission abort decisions are considered based on the degradation level together with the duration in the defective stage. The degradation control limit and time threshold are both dependent on the duration in the normal stage. Mission reliability and system survivability are derived and the structural properties of the optimal abort thresholds minimizing the expected costs of mission failure and system failure are investigated. In addition, we also compare the optimal policy against several heuristic policies where mission reliability and system survivability are evaluated. Numerical studies are presented to validate the obtained results.